Analisa Kepastian Hukum Sertipikat Pengganti Atas Tanah Hak Milik - Mussa Ali Fatullah; Husein Manalu (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The implementation of land registration in society is a state duty organized by the government for the interests of the people. In providing land rights status in Indonesia organized by the Land Office, there are still many people who do not know the procedure procedures if there is a loss of certificates, examples of cases occur in rural areas such as Cibatu Village, South Cikarang, Bekasi, one of its citizens has lost certificates his land. In conducting this research the approach used in solving problems using the empirical juridical approach method. While the empirical approach is to look at the law as a social, cultural, or watershed reality because in this study the data used primary data directly from the study site. Issuance or procedure for certificate of lost land rights must be in accordance with applicable rules. However, in the event that the issuance of a substitute certificate has been set by the laws and regulations as the author has described above, namely it is set in Article 57 paragraph (1) Government Regulation No. 24 of 1997 which states that on the request of a rights holder issued a new certificate as Substitutes of damaged certificates, lost, still use certificate blanks that are no longer used, or that are not handed over to buyers of auction in execution. Substitute certificate holders receive legal protection stipulated in applicable laws and regulations. Legal Protection of Certificate of Land Rights Certificate is the same as the first legal protection of the certificate, if there is no objection or problem in the application process, BPN will submit a replacement certificate to the applicant as the owner of the land object. As stipulated in the Law No. 5 of 1960 Article 19 paragraph (2) letter c, Government Regulation No. 24 of 1997 Article 1 number 20 and Article 32 paragraph (1). Procedure for obtaining a certificate of replacement for lost land rights involves several steps that must be followed in accordance with applicable regulations. Starting from the loss report to the police, the process of blocking the certificate at the land office, to submit a submission of a replacement certificate and verification of documents at the National Land Agency (BPN). The process of issuing a substitute certificate for lost land rights is clearly regulated in applicable laws and regulations, providing legal certainty and protection guarantees for replacement certificates.